INNOVATION, ENTREPRENEURSHIP ORIENTATION, UTILIZATION OF E-COMMERCE, AND INTELLECTUAL CAPITAL ON MSME PERFORMANCE IN THE COVID-19 PANDEMIC - Muhammad Afrinaldi; Yesi Mutia Basri; Aunnur Rafiq (Politeknik Negeri Bengkalis, 2022)
This study aims to analyze the effect of innovation, entrepreneurial orientation, utilization of e-commerce, and intellectual capital on the performance of MSMEs during the COVID-19 pandemic in Pekanbaru City. The data used in this study is primary data, with a questionnaire as an instrument. The method used for sample selection is the non-probability sampling technique. In this study, the total MSMEs in Pekanbaru City affected by COVID-19 was 7888. The research sample was 100 MSMEs. The data analysis technique used in this study is multiple linear regression analysis using Statistical Product and Service Solution (SPSS) data processing software version 26.0. The results show that only innovation, entrepreneurial orientation, and utilization of e-commerce affect MSMEs performance. This research has contributed to MSMEs improving their performance during the COVID-19 pandemic.